Comparative study of subacute combined degeneration of the spinal cord due to nitrous oxide abuse and vitamin B12 deficiency - Agbo, Sedine Marie Desiree Nina; Duan, Xiaohui; Wang, Li; Dong, Mingrui; Wang, Qian; Cai, Xiaojing; Liu, Fang (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study was to compare the clinical presentations, nerve conduction studies, neuroimaging findings of subacute combined degeneration (SCD) caused by N2O abuse and primary vitamin B12 deficiency. The goal is to improve diagnostic accuracy, tailored therapeutic interventions, and ultimately enhancing patient outcomes in cases of SCD caused by N2O abuse.MethodsThis study was a retrospective case-control study which enrolled 23 patients diagnosed with N2O-induced subacute combined degeneration (N2O-SCD) and 20 patients with vitamin B12 deficiency-induced subacute combined degeneration (Vit B12-SCD) between 2015 and 2023. Clinical manifestations, physical examinations, laboratory tests, nerve conduction studies, and spinal cord MRI imaging results were collected. Additionally, age-matched healthy control groups were also included for comparative electrophysiological analysis, consisting of 23 young individuals and 21 elderly individuals corresponding to the N2O-SCD and Vit B12-SCD groups, respectively.ResultsThe study found that compared to Vit B12-SCD, N2O-SCD patients exhibited more severe and extensive neurological damage. Both N2O-SCD and Vit B12- SCD patients may present with numbness or abnormal sensations, limb weakness, difficulty walking and inability to walk, but these are more severe and widespread in N2O-SCD patients. N2O-SCD patients showed significant decreases in limb strength, with common walking difficulties and paralysis. Additionally, N2O abuse patients more frequently exhibited psychiatric symptoms, especially memory loss, hallucinations and confusion. Both Vit B12-SCD and N2O-SCD can cause peripheral nerve demyelination and axonal damage, but it is more severe in the N2O-SCD group, with more damage in the lower limbs than in the upper limbs. The extensive nature of axonal damage also indicated a poor prognosis. The degree of spinal cord damage in the N2O-SCD group was more severe and affected longer segments. These results suggest that in addition to affecting vitamin B12, N2O also causes neurological damage through other mechanisms.ConclusionIn summary, N2O-SCD leads to more severe clinical symptoms, peripheral nerve damage, and spinal cord injury than Vit B12-SCD. These differences guide the clinical treatment of N2O-SCD, requiring not only vitamin B12 supplementation but also an addition in neuroprotective treatments.